Asuhan Keperawatan pada Tn.Y dengan Chronic Kidney Disease Menggunakan Penerapan Terapi Spiritual Emotional Freedom Technique (Seft) untuk Menurunkan Tingkat Kecemasan di Unit Hemodialisa RSUD Embung Fatimah Kota Batam - Maiyuni Susanti; Nelli Roza (Lembaga Pengembangan Kinerja Dosen, 2025)
According to Nature Reviews Nephrology, the prevalence of an aging population faces an increased risk of kidney disease, where current predictions estimate that by 2035 as many as 1.1 billion people will suffer from kidney disease, and has increased since 2020 by 60%. Chronic kidney disease is kidney damage that lasts for a long time (years) and is characterized by a decrease in the kidney's ability to filter blood (GFR). This professional scientific paper aims to provide nursing care to Mr. Y with Chronic Kidney Disease using the application of spiritual emotional freedom technique (SEFT) therapy to reduce anxiety levels in the Hemodialysis Unit of Embung Fatimah Hospital, Batam City. The method used is a case study based on the stages of nursing care including the assessment of HRS-A with a score of 21 (moderate anxiety), with the main nursing diagnosis of anxiety related to situational crises. Nursing interventions and implementations carried out by implementing SEFT therapy during 4 visits obtained the results of the final evaluation of nursing care on Mr. Y showed a decrease in anxiety levels from the first day, the Anxiety Score was 21 and on the fourth day the anxiety score dropped to 12 (no anxiety), and anxiety decreased, tension decreased in accordance with the objectives and criteria. Through the SEFT technique can help reduce anxiety levels. Suggestions for CKD patients as a guide to non-pharmacological therapy in patient care.